PENGARUH KUALITAS PELAYANAN JASA FREIGHT FORWARDING TERHADAP KEPUASAN, KEPERCAYAAN DAN LOYALITAS EKSPORTIR PT ANDALAN PACIFIC SAMUDRA SEMARANG - Erlina DewiKartika Sari; Riyadi - Riyadi; Saptianing - Saptianing (Politeknik Negeri Semarang, 2016)
This research was conducted at PT AndalanPacific Samudra Semarang, a companyengaged in the export import freightforwarding services which always tries togive satisfaction. So it is important for thecompany to build service quality andexporters’ satisfaction to obtain trust withloyalty from exporters of PT Andalan PacificSamudra Semarang. The purpose of thisresearch are to find out the influence offreight forwarding service quality onexporters’ satisfaction, the impact of trustwith loyalty and how much that direct andindirect influence and its impact. Theresearch sample were 34 exporters of PTAndalan Pacific Samudra Semarang asrespondents. The method of analysis in thisresearch were validity test, reliability test, ttest, F test, path analysis test and thecoefficient of determination. The method ofcollecting data are questionnaire andliterature studies. The result of the pathanalysis showed that service quality,satisfaction, trust gave positive andsignificant effect on loyalty exporters. Theresults obtained from testing the hypothesissignificant test, t test and F test, so we couldconclude that service quality significant tosatisfaction, trust and expoters’ loyalty Fromthe results showed the value of the coefficientof determination was 0,845, indicating thatthe service quality, satisfaction, trust had theeffect of 84,5% on loyalty exporters and therest is influenced by other factors which werenot examined